Pengaruh Pengetahuan, Kesadaran Pajak, Dan Sanksi Pajak Terhadap Kepatuhan Wajib Pajak Orang Pribadi Pada Kantor Pelayanan Pajak Pratama Pangkalan Kerinci - Rahayu, Fitri; Surya, R. Adri Satriawan; Supriono, Supriono (Sekolah Tinggi Ilmu Ekonomi Riau, 2023)
The purpose of this study was to the influence of tax knowledge, awareness of taxpayers and tax sanctions on the complience of individual taxpayers who carry out business activities and freelance jobs at KPP Pratama Pangkalan Kerinci. The sample in this study were who carry out business activities and freelance jobs at KPP Pratama Pangkalan Kerinci totaling 100 people. Analysis of data using multiple linear regression method using validity test, reliability test, normality test, heteroscedasticity test, multicollinearity test, F test, t test, and R2 test. The tests are conducted to determine the relationship between the independent variables (independent variables) and dependent variable (dependent variable). Based on the results obtained adjusted value R-square at 0.764 which can mean tax knowledge, awareness of tax payers and tax sanctions has a contribution of 76.4% contribution of taxpayer complience at KPP Pratama Pangkalan Kerinci. Simultaneously tax knowledge, awareness of tax payers and tax sanctions variabel affect taxpayer complience at KPP Pratama Pangkalan Kerinci. Partially obtained tax knowledge significant effect on taxpayer complience at KPP Pratama Pangkalan Kerinci with t value 5.247 > t table 1.985, obtained awareness of tax significant effect on taxpayer complience at KPP Pratama Pangkalan Kerinci with t value 3.896 > t table 1.985 and obtained tax sanctions significant effect on taxpayer complience at KPP Pratama Pangkalan Kerinci with t value 2.224 > t table 1.985